Biological responses of confused flour beetle, tribolium confusum (duval.) (coleoptera: tenebrionidae) to ultrasound emitting device - Salem, Mohamed S.; El-Massrawy, Salah A.; El-Wassef, Reham A. M. (2006)
The use of ultrasonic sound (ultrasound) to eliminate or manage pests in the near environment has been widely publicized over the past three years. As interest and confusion in the use of ultrasound persist, public and private organizations have come under increased pressure to provide recommendations, regarding this technology (Dunn, 1982, Rambo, 1982 and Miller 1983). Research on the use of ultrasound in agricultural and urban environments has been limited. Use of radiation to disinfest agricultural products has obvious advantages. most of which are influenced by environmental, cultural, commercial and governmental factors. Nakakita (1982) found that Tribolium castaneum (Herbst) is cosmopolitan and experimental stored- product insect, whereas T. freeman (Hinton) is a new potential pest in stored products. Under crowded conditions, the last larval instar of T. freemani fails to pupate and instead enters a series of Stationary moults that may continue for more than 6 months. Although these insects are of the same genus and both are stored product pests, they respond differently to the effect of larval population density. Pulsed ultrasound was used with limited success to influence the behavior of various lepidopteran crop pests. Adults of the cotton bollworm, Heliothis zea, exhibited erratic flight patterns and evasive behavior when exposed to pulsed ultrasound both in caged and field experiments (Agee, 1969, Agee and Webb, 1969). Ultrasound caused mortality in adult, larvae and increased larval and pupal duration. Also, cholinesterase decreased with active ultrasonic- emitting device (Salem et al., 2006). The responses of several non - stored product moths to ultrasound, and limited evidence on Plodia interpunctella male responses to ultrasound (Trematerra and Pavan, 1995), suggest that the use of this technology may he a promising nonchemical pest management method. By reducing the chance of successful mating, populations may be reduced to a level where they do not cause economic damage to stored products. In our laboratory, detailed studies are under way to characterize the effects of ultrasound on larval duration and pupal stage, adult body weight under isolated and crowded conditions, fecundity and pupal malformations were studied.
Includes references.
1
Keywords: Confused flour beetle -- Behavior; Confused flour beetle -- Control; Ultrasonics